Pancreatic ductal adenocarcinoma: Risk factors, screening, and early detection - Becker, Andrew E (Baishideng Publishing Group Inc, 2014)
Pancreatic cancer is the fourth most common cause of cancer-related deaths in the United States, with over 38000 deaths in 2013. The opportunity to detect pancreatic cancer while it is still curable is dependent on our ability to identify and screen high-risk populations before their symptoms arise. Risk factors for developing pancreatic cancer include multiple genetic syndromes as well as modifiable risk factors. Genetic conditions include hereditary breast and ovarian cancer syndrome, Lynch Syndrome, familial adenomatous polyposis, Peutz-Jeghers Syndrome, familial atypical multiple mole melanoma syndrome, hereditary pancreatitis, cystic fibrosis, and ataxia-telangiectasia; having a genetic predisposition can raise the risk of developing pancreatic cancer up to 132-fold over the general population. Modifiable risk factors, which include tobacco exposure, alcohol use, chronic pancreatitis, diet, obesity, diabetes mellitus, as well as certain abdominal surgeries and infections, have also been shown to increase the risk of pancreatic cancer development. Several large-volume centers have initiated such screening protocols, and consensus-based guidelines for screening high-risk groups have recently been published. The focus of this review will be both the genetic and modifiable risk factors implicated in pancreatic cancer, as well as a review of screening strategies and their diagnostic yields.